2022
DOI: 10.1186/s13046-021-02167-3
|View full text |Cite
|
Sign up to set email alerts
|

Different pancreatic cancer microenvironments convert iPSCs into cancer stem cells exhibiting distinct plasticity with altered gene expression of metabolic pathways

Abstract: Background Cancer stem cells (CSCs) are generated under irregular microenvironment in vivo, of which mimic is quite difficult due to the lack of enough information of the factors responsible for cancer initiation. Here, we demonstrated that mouse induced pluripotent cells (miPSCs) reprogrammed from normal embryonic fibroblasts were susceptible to the microenvironment affected by cancer cells to convert into CSCs in vivo. Methods Three different pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…We demonstrated that CM from different cells of human cancer cell lines was rich in growth factors and cytokines that could convert mouse iPSCs into CSCs (Afify et al 2020 ; Calle et al 2016 ; Chen et al 2012 ; Hassan et al 2022 ). Further, we showed that microenvironment of pancreatic cancer cell line BxPC3 cells converted mouse iPSCs into aggressive CSCs (Hassan et al 2022 ). In this context, microenvironments of different pancreatic cancer cell line cells could convert mouse iPSCs into different CSCs with different plasticity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We demonstrated that CM from different cells of human cancer cell lines was rich in growth factors and cytokines that could convert mouse iPSCs into CSCs (Afify et al 2020 ; Calle et al 2016 ; Chen et al 2012 ; Hassan et al 2022 ). Further, we showed that microenvironment of pancreatic cancer cell line BxPC3 cells converted mouse iPSCs into aggressive CSCs (Hassan et al 2022 ). In this context, microenvironments of different pancreatic cancer cell line cells could convert mouse iPSCs into different CSCs with different plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…The hiPSCs in day 0 and after four weeks of conversion were cultured on gelatin coated dishes in DMEM media (Wako, Japan) with 15% FBS. The primary cultures of cells from tumors were prepared as same as described previously (Hassan et al 2022 ). After digestion, 3 ml of StemFit Basic 03 medium with 10% FBS was added to stop digestion.…”
Section: Materials S and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, both the presence and the abundance of nutrients within the local microenvironment may determine the metabolic phenotype that cancer cells adopt to accomplish each stage of the metastatic process. Indeed, ECM detachment causes defective glucose utilization, reduces pentose phosphate pathway (PPP), diminishes adenosine triphosphate (ATP) production, and increased ROS generation [13][14][15]. Despite advances in this field during the last decade, nutrient demands and related mechanisms that sustain the survival of cancer cells following ECM detachment have not been sufficiently elucidated.…”
Section: Introductionmentioning
confidence: 99%